Why Monitoring Doesn't Always Matter: The Interaction of Personal Propensity with Physical and Psychological Parental Presence in a Situational Explanation of Adolescent Offending. Issue 3 (4th March 2021) - Hardie, Beth
ABSTRACT: Parental monitoring is often shown to have a negative relationship with crime involvement. However, research often ignores both the mechanism by which these relationships occur and the conditions under which they might (and might not) be found. Building on the interactional hypotheses of Situational Action Theory (SAT) and the parental monitoring definitions provided by a new model of Goal-Directed Parental Action (GDPA), this paper assesses evidence of the role of the presence or absence of guardians, adolescent-perceived parental knowledge and personal crime propensity in explaining why a crime does or doesn't occur in a particular situation. To test these new hypotheses, this paper uses specialist data (including innovative Space-Time Budget data) from the Peterborough Adolescent and Young Adult Development Study (PADS+) and employs multiple methods to assess both statistical interaction (dependence) and situational interaction (convergence). Findings provide evidence for interaction between key personal characteristics (specifically, generalized law relevant morality and ability to exercise self control) and features of environments (in this study, aspects of parental monitoring) in the perception-choice process that is proposed by SAT to explain action, including acts of crime. They suggest that despite high correlations with crime in the literature, monitoring doesn't always matter because many crime averse young people do not offend anyway. Furthermore, in an entirely new finding, generalized perceived parental knowledge of the circumstances of activity (psychological presence) results in a lower rate of crime among crime prone adolescents when they are unsupervised.